Genotype-Phenotype Characteristics of Children with Distal Renal Tubular Acidosis Caused by WDR72 Mutations: A Systematic Review of Case Reports - Mugdha Todkar; S Harshitha; Girish Chandra Bhatt (Wolters Kluwer Medknow Publications, 2023)
Background: Distal renal tubular acidosis (dRTA) can be acquired or inherited. Hereditary types of dRTA are mostly seen in the pediatric population, whereas acquired forms predominate in adults. The diagnosis of hereditary dRTA can be confirmed by genetic testing. Five genes are known to cause the disease: ATP6V1B1, ATP6V0A4, FOXI1, SLC4A1, and WDR72. Most of the children with autosomal dominant forms carry mutations in the SLC4A1 gene, whereas the most common mutation in autosomal recessive type is ATP6V0A4 and ATP6V1B1 genes. Objective: In this systematic review of case reports, we discuss the clinical features and mutation variants of hereditary dRTA due to homozygous pathogenic variations in the WDR72 gene, which has been recently identified. Methods: The PubMed and Google Scholar databases were searched with defined search terms and eligibility criteria independently by different authors. Results: Of five full-text articles retrieved, four were finally included which provided data of 14 individuals, all of which had specific mutations in WDR72 gene. The majority of cases were attributed to individuals of Asian descent (71%) with equal distribution of males and females. The mean age of onset was 4.42 years. Amelogenesis imperfecta (AI) was described in 90% of patients, nephrocalcinosis in 62.5%, polyuria in 55.5%, proximal muscle weakness in 55.5%, and rickets in two patients. Conclusion: In patients exhibiting features such as metabolic acidosis, hypokalemia, AI, polyuria, nephrocalcinosis, and growth retardation, genetic analysis for WDR72 mutation should be considered.